Implementing IR 4.0 Based-Teaching Model through Kahoot: A Case Study of State Elementary School 1 of Sukoharjo - Veronika Unun Pratiwi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The use of learning media is one of the main achievements to teaching process in the age of Industrial Revolution 4.0 (IR 4.0). Through media, students can understand more easily what a teacher explains in the course of learning, both in class and elsewhere. In teaching English reading to students of Elementary School Jombor 1 of Sukoharjo, at the end of each learning process, each teacher of 13 respondents was given a time to conduct a study assessment to assess the degree to which students' skills are based on the responses of teachers regarding what is demonstrated in a number of ways, including by presenting questionnaires, group presentations, written assessments by using Kahoot App. The English quizzes provided by Kahoot App can increase students' desire to learn, and learning innovations and students' participation in the reading learning process. The success of this newly used of method need to integrate teachers and students’ active participation in creating an effective learning technology environment.